Experiment‐Oriented Materials Informatics for Efficient Exploration of Design Strategy and New Compounds for High‐Performance Organic Anode. Issue 10 (6th September 2019) - Numazawa, Hiromichi; Igarashi, Yasuhiko; Sato, Kosuke; Imai, Hiroaki; Oaki, Yuya
Abstract: High‐performance organic energy storage has attracted much interest as a future battery. Organic anode has been developed as an alternate of graphite in the past decade. However, the design strategies are not fully studied for further development. The present work shows experiment‐oriented materials informatics (MI) for efficient exploration of design strategy and new compounds for an active material of high‐performance organic anode. A few important factors to achieve high specific capacity are extracted from training dataset containing experimentally measured specific capacity, calculation results, and literature data of the model compounds using sparse modeling, an informatics approach. Although the prediction model is not sufficiently accurate, the model assists in exploration of new compounds in combination with experience and intuition of experimental scientists. New compounds with high specific capacity, such as 227 mA h g –1 at 100 mA g –1 for benzo[1, 2‐b:4, 5‐b′]dithiophene (BdiTp), are efficiently discovered in a minimum number of experiments. Furthermore, polymerization of BdiTp exhibits the enhanced performances, such as 933 mA h g –1 at 20 mA g –1 and cycle stability, and rate performance. MI combined with experiment, calculation, and data accelerates design new materials and functions by experimental scientists having their small data, experience, and intuition. Abstract : A new experiment‐oriented materials informatics combined with experience and intuition of experimental scientists is applied to explore general design strategy and discover new compounds for high‐performance organic anodes as an alternate of graphite for lithium‐ion battery. Furthermore, polymerization of the discovered compound realized the enhanced specific capacity, cycle stability, and rate performance.